Quantificação do carbamato de etila em cachaças produzidas em diferentes sistemas de produção agroindustrial - D'Avila, Gabriel Biscotto (2015)
Popularly known by various names such as caninha, dangerous, drips, damned and many other denominations, cachaça is the genuine Brazilian drink, produced by fermentation of sugar cane juice by yeast, followed by distillation in alambics. Considering that cachaça is the most widely consumed distilled beverage from Brazil, the knowledge of the chemical composition and the presence of potentially toxic compounds such as ethyl carbamate, considered a human carcinogen, is important. The aim of this study was to evaluate the influence of different conditions of the agro-industrial production systems of cachaça, including the variety of sugarcane, on the quantification of ethyl carbamate through the chromatographic profile and physical-chemical analysis. Thirteen unaged beverage samples produced from different varieties of sugar cane were analyzed. Using analysis of variance and comparison of average concentrations of ethyl carbamate (Scott-Knott, α = 5%), all the samples were found to contain contaminant levels below the ceiling established by the legislation, which is 210 μg L -1.